Application of Quick Response Code Indonesian as a Payment Tool in Digitizing MSMEs - Anggarini, Desy Tri (Universitas Muhammadiyah Sorong, 2022)
The purpose of the research is to contribute to the development of technology in the financial sector, to give influence to the community in terms of cashless, then also to provide insight into financial technology on financial literacy by using QRIS (Quick Response Code Indonesian). MSMEÂ use facilitate their business activities by implementing fintech in terms of transaction management and the role of financial technology, is the QRIS (Quick Response Code Indonesian) application as a means of payment. The research method used in the research on the application of QRIS (Quick Response Code Indonesian) as a Payment Tool in digitizing MSMEs is a qualitative descriptive study using field research methods. This study uses interviews with 10 traders and 10 UMKM consumers who use QRIS. The research location is in BSD Modern Market, using non-probability techniques. Primary data taken directly from the object of research. With the direct observation method at the BSD modern market, South Tangerang with interview techniques for both consumers and traders who use QRIS as well as secondary data also obtained through various literatures. The result of the research is that QRIS as a digital payment tool for MSMEs is non-cash digital payment using Gopay, Ovo and others. QRIS has the potential to expand MSME sales, with QRIS an increase in digital sales traffic and a decrease in cash, minimizing the risk of paying counterfeit money, automatically recording transactions, building credit profiles for banks, making it easier to get working capital, payment of retribution, bills, purchasing goods in cash easily.